The effect of selenium on the proliferation of bovine endometrial epithelial cells in a lipopolysaccharide-induced damage model - Hanqing Li; Heng Wang; Luying Cui; Kangjun Liu; Long Guo; Jianji Li; Junsheng Dong (BMC Veterinary Research, 2024)
Abstract Background Endometritis is a common bovine postpartum disease. Rapid endometrial repair is beneficial for forming natural defense barriers and lets cows enter the next breeding cycle as soon as possible. Selenium (Se) is an essential trace element closely related to growth and development in animals. This study aims to observe the effect of Se on the proliferation of bovine endometrial epithelial cells (BEECs) induced by lipopolysaccharide (LPS) and to elucidate the possible underlying mechanism. Results In this study, we developed a BEECs damage model using LPS. Flow cytometry, cell scratch test and EdU proliferation assay were used to evaluate the cell cycle, migration and proliferation. The mRNA transcriptions of growth factors were detected by quantitative reverse transcription-polymerase chain reaction. The activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and Wnt/β-catenin pathways were detected by Western blotting and immunofluorescence. The results showed that the cell viability and BCL-2/BAX protein ratio were significantly decreased, and the cell apoptosis rate was significantly increased in the LPS group. Compared with the LPS group, Se promoted cell cycle progression, increased cell migration and proliferation, and significantly increased the gene expressions of TGFB1, TGFB3 and VEGFA. Se decreased the BCL-2/BAX protein ratio, promoted β-catenin translocation from the cytoplasm to the nucleus and activated the Wnt/β-catenin and PI3K/AKT signaling pathways inhibited by LPS. Conclusions In conclusion, Se can attenuate LPS-induced damage to BEECs and promote cell proliferation and migration in vitro by enhancing growth factors gene expression and activating the PI3K/AKT and Wnt/β-catenin signaling pathways.